Impact of an educational intervention on improving the Nursing Activities Score in Neonatology (Research, Society and Development, 2021)
Aim: To compare the Nursing Activities Score (NAS) scores obtained in 2015 and 2016 in a Neonatal ICU (NICU) after an educational intervention with nurses. Method: Retrospective, comparative, before-and-after study. Sample consisted of secondary data from NAS scores, from January 2015 to December 2016. Data analysis through descriptive statistics and t-Student test (P